2001
DOI: 10.1542/peds.107.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Outbreak at a Summer Camp for Human Immunodeficiency Virus-Infected Children

Abstract: Widespread varicella transmission occurred at the camp. A case of zoster was the most likely source. The risk for such outbreaks can be minimized through vaccinating susceptible staff members, considering vaccination for asymptomatic or mildly symptomatic HIV-infected children according to Advisory Committee on Immunization Practices and American Academy of Pediatrics guidelines, rigorously collecting recent varicella and zoster exposure information, excluding anyone with active varicella or zoster or with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…There are two published reports of varicella outbreaks at summer camps (23,24). The first occurred in Connecticut in 1997 at a camp for HIV-infected children.…”
Section: Does Vzv Go To Camp?mentioning
confidence: 99%
“…There are two published reports of varicella outbreaks at summer camps (23,24). The first occurred in Connecticut in 1997 at a camp for HIV-infected children.…”
Section: Does Vzv Go To Camp?mentioning
confidence: 99%
“…The most serious outbreak of infection at an HIV/AIDS camp was reported in 2001 by Winquist et al Varicella infected 36% of the campers, and the index case was believed to be a child with active Zoster. The authors concluded, however, that an HIV/AIDS camp could be safe given proper vaccination, screening, and other precautions 12.…”
Section: Discussionmentioning
confidence: 97%
“…Reports of VZV outbreaks in HIV‐positive children are well documented (1–4). However, we present a case of a 10‐year‐old boy with previously undiagnosed HIV until presenting with disseminated varicella.…”
Section: Discussionmentioning
confidence: 99%